نحو تجريم ظاهرة الغش في الامتحانات (El-Wahat Journal for Research and Studies, 2015)
criminalizing the phenomenon of cheating in exams criminalizing the phenomenon of cheating in exams we wanted subject from which the light on the phenomenon took root in Algerian society, and affected different segments, the phenomenon was a few years ago is actually disapproving and unethical and values become commonplace, it's getting old and young, educated and limited the level of science and ignorant today.Because of the dangerous dimensions of this phenomenon as affecting the credibility of state institutions must be re-examination of the legal system governed by, and to find preventive solutions that prevent their occurrence, and deterrence to reduce and control.